The effect of oxidative stress inhibition with trimetazidine on the peritoneal alterations induced by hypertonic peritoneal dialysis solution - Günal, AI; Celiker, H; Ustundag, B; Akpolat, N; Dogukan, A; Akcicek, F (Wichtig Editore, 2003)
Background: Chronic peritoneal dialysis (PD) can result in several peritoneal alterations of varying degree, which lead to progressive reduction in dialytic efficacy. Although its pathogenesis has not been clarified yet, it has been proposed that high glucose induced oxidative stress generation within the peritoneal membrane plays an important role in leading to membrane alterations. The aim of this study was to investigate the effect of oxidative stress inhibition on peritoneal alterations induced by hypertonic PD solutions in rats. Methods: The rats were divided into three groups receiving no treatment (the control group), hypertonic PD solution intraperitonealy (ip) only (the hypertonic dextrose group) and hypertonic PD solution ip plus trimetazidine (TMZ) orally (TMZ group). After 4 weeks, a one-hour peritoneal equilibration test (PET) was performed. Dialysate-to-plasma urea ratio (D/P urea), glucose reabsorption (D-1/D-0 glucose), ultrafiltration volume (UF) and the level of dialysate protein were determined. The levels of malondialdehyde (MIDA), vascular endothelial growth factor (VEGF) and the activity of glutathione peroxidase (GPx) were investigated in the peritoneal tissue lysates. The peritoneal membrane was evaluated histologically by light microscopy. Results: Compared to the control group, peritoneal function tests (LTF: 3.6 +/- 0.4 vs. 1.2 +/- 0.6 mL, D/P urea: 0.57 +/- 0.03 vs. 0.76 +/- 0.04, D-1/D-0 glucose: 0.46 +/- 0.02 vs. 0.33 +/- 0.05) and morphology (thickness: 4.4 +/- 0.5 vs. 61 +/- 14 mum and neovascularisation: 0.2 +/- 0.4 vs 2.4 +/- 0.8 number/field) were dramatically altered in the hypertonic PD solution-treated rats. Likewise, higher levels of VEGF, MDA and decreased activity of GPx were determined in the hypertonic PD solution-treated rats. Although peritoneal thickness (37 +/- 17 mum) was not completely decreased, peritoneal functions were protected in the TMZ group (UF: 4.0 +/- 0.4 mL, D/P urea: 0.62 +/- 0.06, D-1/D-0 glucose: 0.43 +/- 0.02). In the TMZ group, MDA and VEGF levels and neoangiogenesis were significantly less than those of the hypertonic dextrose group. In addition, GPx activity significantly increased in the TMZ group. Conclusion: These data demonstrated that not only generating oxidative stress but also attenuating antioxidative system and high glucose concentration can cause structural and functional alterations within the peritoneal membrane. TMZ can preserve these alterations by inhibiting the oxidative stress within the peritoneal membrane.
Keywords: CAPD; glucose-based dialysis solutions; oxidative stress; malondialdehyde; glutathione peroxidase; VEGF; trimetazidine